Sleepy Sheepy and the sheepover (Sleepy Sheepy, ,, 2024)
Sleepy Sheepy is excited for his first sleepover at Grammy and Grampy's house, but when it is time to go to bed he misses home too much to fall asleep.

Oh, are you awake? (Candlewick Press, 2024)
There once was a very sleepy penguin, who was best friends with a not-so-sleepy lion... A pitch-perfect comedy for anyone who has ever craved sleep -- and anyone too full of energy to settle down.